PENGGUNAAN METODE BERMAIN DENGAN KARTU KATA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA ANAK - Nunik Wiharyanti; Rahmat Mulyono (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
Language development in Early Childhood includes expressive language and receptive language. The ability to read in children is included in receptive language. Based on the results of observations at Budi Mulia Dua Sedayu Kindergarten that the use of playing techniques using letter cards is a separate motivation for children to learn to recognize words and learn to read while playing. This research is a qualitative descriptive study that is used to describe reading techniques using word cards which are carried out using the playing method. The subjects in this study were group B children at Budi Mulia Dua Sedayu Kindergarten. The data obtained from this study were obtained from teacher interviews, observations, and documentation. The techniques used in conducting data analysis are data reduction, data presentation, and drawing conclusions. The results of the study obtained the final data that the ability of children who were originally included in the Undeveloped (BB) criteria in reading ability was progressing about 59%. The conclusion from the results of this study is that word cards given using playing methods are effective for improving children's reading skills if teachers and parents work together to motivate children to learn to read and there is a child's willingness to learn.